VOCATIONAL AND SENIOR HIGH SCHOOL PROFESSIONAL TEACHERS IN INDUSTRY 4.0 - Sunaryo Soenarto; Sugito Sugito; Suyanta Suyanta; Siswantoyo Siswantoyo; Marwanti Marwanti (Jurnal Cakrawala Pendidikan, 2020)
The teacher certification program has been implemented since 2007, yet the society has not optimally experienced the quality improvement of secondary education in Industry 4.0. This study aims to examine vocational and senior high school teacher professionalism in the age of Industry 4.0 in developing learning. This study employed the survey method with quantitative descriptive analysis. The sample of this study was taken from two provinces in Indonesia, namely Yogyakarta Special Region and West Borneo. The data were collected from 113 vocational and senior high school teachers using random purposive sampling. The instruments used in this research were open-ended and close-ended questionnaires. The results of this study show that there is still a low number of teachers with a Master’s degree; however, teachers participate in various capacity building training programs. Moreover, the most common training programs for the teachers are on classroom action research, scientific journal publications, curriculum development, and updating teaching materials. Furthermore, it is found that the number of journal articles published by vocational and senior high school teachers in the two provinces is still low, and as a result, bottleneck problems may occur in their career promotion.